THE IMPORTANCE OF SOCIO-PHILOSOPHICAL VIEWS OF FERGANA JADID SCHOOL REPRESENTATIVES IN BUILDING NEW UZBEKISTAN AND CIVIL SOCIETY (Scientific journal of the Fergana State University, 2026)
This article analyzes the socio-philosophical views of the representatives of the Fergana Jadid school in the process of building a civil society in the conditions of New Uzbekistan, their role in the formation of national identity, spiritual growth, and independent thinking, and highlights the ideas of the Jadids in connection with modern democratic principles, their significance in the development of free thinking, educational reforms, and civic consciousness.